2009
DOI: 10.1161/strokeaha.108.528356
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor I

Abstract: Background and Purpose-Insulin-like growth factor I (IGF-I) exerts neuroprotective effects in both white and gray matter under different detrimental conditions. The purpose of this review is to collect the evidence whether IGF-I is a candidate neuroprotective drug in patients with acute ischemic stroke. Results-IGF-I was found to be neuroprotective in animal models of focal brain ischemia when given Ն2 hours after the insult. Different routes of administration (eg, cerebroventricular, intravenous, and intranas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…Due to this high expression, among the factors presently investigated, IGF-1 is thought to play a pivotal role in the amelioration of ischemic damage. The amount of the BINC-derived IGF-1, however, may be insufficient to maximize its neuroprotective ability, in view of several reports showing that exogenously administrated IGF-1 still can give marked amelioration of ischemic brain damage (Kooijman et al, 2009). As shown in Figure 5, the cell density of BINCs in the infarcted cerebellar tissue from the elderly patient was far less than that in ischemic lesions of 8-weekold rats, even though the human tissue was obtained 4 days after symptom onset when the accumulation of BINCs was not yet at its maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this high expression, among the factors presently investigated, IGF-1 is thought to play a pivotal role in the amelioration of ischemic damage. The amount of the BINC-derived IGF-1, however, may be insufficient to maximize its neuroprotective ability, in view of several reports showing that exogenously administrated IGF-1 still can give marked amelioration of ischemic brain damage (Kooijman et al, 2009). As shown in Figure 5, the cell density of BINCs in the infarcted cerebellar tissue from the elderly patient was far less than that in ischemic lesions of 8-weekold rats, even though the human tissue was obtained 4 days after symptom onset when the accumulation of BINCs was not yet at its maximum.…”
Section: Discussionmentioning
confidence: 99%
“…GH and IGF1 have many similar effects in the brain. For example, in rodents, both GH (Gustafson et al 1999, Scheepens et al 2001, Pathipati et al 2009) and IGF1 (Guan et al 2001, Lin et al 2005, Kooijman et al 2009) have been shown to protect the brain against hypoxic-ischemic (HI) injuries. Circulating IGF1 is believed to mediate some of the effects of GH on the brain (for review, see Å berg et al (2006)).…”
Section: Oprd1mentioning
confidence: 99%
“…IGF-I has been shown to be a potent neuroprotective compound in rodent models of ischemic stroke. 1 Most of the circulating IGF-I is found in a 150 kDa complex consisting of insulin-like binding protein 3 (IGFBP3), IGF-I, and an acid-labile subunit, which transports IGF-I in the circulation and prolongs its half-life. IGF-I is available for clinical use but has not been studied in a clinical trial in patients with stroke.…”
mentioning
confidence: 99%